2021
DOI: 10.3390/ijms22041563
|View full text |Cite
|
Sign up to set email alerts
|

Plasma miR-9-3p and miR-136-3p as Potential Novel Diagnostic Biomarkers for Experimental and Human Mild Traumatic Brain Injury

Abstract: Noninvasive, affordable circulating biomarkers for difficult-to-diagnose mild traumatic brain injury (mTBI) are an unmet medical need. Although blood microRNA (miRNA) levels are reportedly altered after traumatic brain injury (TBI), their diagnostic potential for mTBI remains inconclusive. We hypothesized that acutely altered plasma miRNAs could serve as diagnostic biomarkers both in the lateral fluid percussion injury (FPI) model and clinical mTBI. We performed plasma small RNA-sequencing from adult male Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 94 publications
0
33
0
Order By: Relevance
“…In this context, miRNAs found in blood and body fluids are currently gaining attention [ 88 ]. Circulating miRNAs appear to be good candidates in biomarker research due to their high level of stability in the blood [ 89 , 90 ] and the presence of brain-specific miRNA transcripts, such as miR-9, that can be detected in body fluids [ 91 ]. Indeed, numerous scientific reports have shown that brain-specific miRNAs can effectively cross the blood–brain barrier and are detectable in blood [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], as well as in brain-derived extracellular vesicles circulating in the bloodstream [ 93 ].…”
Section: Mirna Studies Of Depression and Antidepressant Treatments Investigating Blood And Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, miRNAs found in blood and body fluids are currently gaining attention [ 88 ]. Circulating miRNAs appear to be good candidates in biomarker research due to their high level of stability in the blood [ 89 , 90 ] and the presence of brain-specific miRNA transcripts, such as miR-9, that can be detected in body fluids [ 91 ]. Indeed, numerous scientific reports have shown that brain-specific miRNAs can effectively cross the blood–brain barrier and are detectable in blood [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], as well as in brain-derived extracellular vesicles circulating in the bloodstream [ 93 ].…”
Section: Mirna Studies Of Depression and Antidepressant Treatments Investigating Blood And Bodymentioning
confidence: 99%
“…Circulating miRNAs appear to be good candidates in biomarker research due to their high level of stability in the blood [ 89 , 90 ] and the presence of brain-specific miRNA transcripts, such as miR-9, that can be detected in body fluids [ 91 ]. Indeed, numerous scientific reports have shown that brain-specific miRNAs can effectively cross the blood–brain barrier and are detectable in blood [ 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ], as well as in brain-derived extracellular vesicles circulating in the bloodstream [ 93 ]. The ability of brain-specific miRNAs to pass through the blood–brain barrier makes them ideal biomarkers of brain processes, including mental illnesses such as depression.…”
Section: Mirna Studies Of Depression and Antidepressant Treatments Investigating Blood And Bodymentioning
confidence: 99%
“…The miR-425-5p could possibly be useful in controlling the negative effects of ischemic stroke, as Lim reported (55). The mmu-miR-434-3p has been suggested to potentially increase neuronal regeneration under conditions of stress, especially in brain injury (56)(57)(58). The miR-453 was found to be a good outcome associated with neural repair during ischemic stroke recovery (59,60).…”
Section: Discussionmentioning
confidence: 83%
“…44 The miR-9-3p is upregulated in the brain tissue of IS patients, 45 and it may be a diagnostic marker for experimental and human mild head injury. 46 MiR-9 upregulation may target the expression of BDNF to promote neurodegeneration of dopaminergic neurons caused by neurotoxins and cell apoptosis. 47 Hypoxia or reoxygenation downregulate miR-374a-3p in endothelial cells, 48 so future work should explore whether this downregulation is associated with IS.…”
Section: Discussionmentioning
confidence: 99%